2019
DOI: 10.1021/acsbiomaterials.9b00636
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3D-Printed Drug-Eluting Stent for Treating Obstructive Salivary Gland Disease

Abstract: Most studies of obstructive salivary gland disease have reported only statistical aspects, surgical operations, and prescriptions and have simulated the phenomena occurring in the salivary glands and ductal tissues. However, no direct lesion treatments involving drug-eluting stents have been used to reduce salivary pooling induced by inflammation. In this study, a biodegradable polymer polycaprolactone (PCL)-based antibiotic-eluting stent was developed to treat recurrent obstructive salivary gland disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 53 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…Conceptual illustration of the typical pathway from identifying the target physiological defects, identifying and selecting suitable material(s), fabricating, and characterizing the scaffold, and applying it to the specific biomedical problem, as well as biomedical application fields, where biodegradable polymer scaffolds will address the clinical problem. Insets: refs , . Reproduced with permission from ref .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptual illustration of the typical pathway from identifying the target physiological defects, identifying and selecting suitable material(s), fabricating, and characterizing the scaffold, and applying it to the specific biomedical problem, as well as biomedical application fields, where biodegradable polymer scaffolds will address the clinical problem. Insets: refs , . Reproduced with permission from ref .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Reproduced with permission from ref . Copyright 2020 IOP Publishing, Ltd. Reproduced with permission from refs , . Copyright 2018 and 2019 American Chemical Society.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Drug-eluting stents (DES) can not only physically provide structure to keep the blood vessel open, but also release multiple therapeutics designed to treat post-surgical side effects such as inflammation. Therapeutics can be blended with polymers to create a drug-loaded filament for 3D printing, or coated on the surface of printed stents [ 121 ]. Kim et al developed a 3D printed PCL DES, using a deposition-based 3D printer, to treat recurrent obstructive salivary gland disease, commonly caused by the buildup of salivary stones [ 121 ].…”
Section: D Printing In Parenteral Applicationsmentioning
confidence: 99%
“…Therapeutics can be blended with polymers to create a drug-loaded filament for 3D printing, or coated on the surface of printed stents [ 121 ]. Kim et al developed a 3D printed PCL DES, using a deposition-based 3D printer, to treat recurrent obstructive salivary gland disease, commonly caused by the buildup of salivary stones [ 121 ]. The stent shape was derived from CT images to mimic salivary ducts after removal of salivary stones.…”
Section: D Printing In Parenteral Applicationsmentioning
confidence: 99%
“…The braided PCL stents showed superior compression properties and recovery ability by incorporating PPDO monofilaments and annealing, but their degradation rates were attenuated under dynamic loading (Zhao et al, 2018(Zhao et al, , 2019. Kim et al (2019) investigated drug-eluting PCL mesh network tubular stent for salivary gland disease. Results showed that their mechanical properties were improved by incorporating antibiotic particles, and a sustained drug release was observed.…”
Section: Introductionmentioning
confidence: 99%